Evaluation of Mutagenicity and Carcinogenicity of Opium Using the Ames Test - Mahnaz Mottaghi; Kyumars Safinejad; Hassan Mohammad Asghari (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2017)
Introduction: Cancer is one of the most common diseases in the world. Due to the carcinogenic combinations of drug, there is a risk of mutagenic substances in consumers. The aim of this study was to investigate the mutagenicity of opium by the Ames test. Methods: Firstly, the purity of the Salmonella typhimurium strain TA100 was confirmed in terms of purity of mutagenic properties. Then, samples of opium were prepared separately in different volumes and by various repetitions and were added to the culture medium containing TA100 fresh night culture, after that subsequently were compared with negative control (distilled water+ TA100) samples. In that case, colonies were evaluated in terms of mutagenicity in three stages: without the buffer microsomal rat liver (S9) -without pre incubation, with S9– with pre incubation and with S9- without pre incubation. The colonies were evaluated by counting revertant TA100 colonies number. The results were analyzed using ANOVA and Schefe's post hoc test to determine and prioritize the difference in mean of groups based on opium dilution. Results: Results of data analysis and counting of revertant coloniesshowed that opium had mutagenic effect in over 4% dilution. There were significant differences in dilution and repetition of without S9- without pre incubation, with S9- with pre incubation and with S9 without pre incubation compared to the negative controls. Conclusion: The results of this research showed that opium is fully and on all volumes has mutagenic effect. Therefore, we recommend taking these drugs should be avoided.